2016
DOI: 10.1021/acsphotonics.6b00060
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Optical Tamm States: A Step toward a Full Molecular–Dielectric Photonic Integration

Abstract: High reflectance in heavily doped polymer films as a function of oscillator strength Observation of a metallic lustre in a thin film is possible when the value of the real part of the permittivity of the material is negative enough. In a material described by a Lorentzian expression the restricted wavelength range where the real part of the permittivity of a material is negative to show a high reflectance response, depends strongly on the oscillator strength. The figure 1 shows the simulated reflection using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…These attractive characteristics of the optical Tamm structures already led to a variety of their applications in optoelectronics and photonics, including amplitude-based optical sensing 32,37,38 , development of metal/semiconductor lasers [39][40][41] , etc. [42][43][44][45][46][47][48][49] .…”
mentioning
confidence: 99%
“…These attractive characteristics of the optical Tamm structures already led to a variety of their applications in optoelectronics and photonics, including amplitude-based optical sensing 32,37,38 , development of metal/semiconductor lasers [39][40][41] , etc. [42][43][44][45][46][47][48][49] .…”
mentioning
confidence: 99%
“…Most of them are based on a TP coupling with other excitations, including a SP [5][6][7], Bragg cavity mode [8,9], exciton confined either in a quantum well [10] embedded inside the BM or in a monolayer of the transition-metal dichalcogenide [11,12], and also point emitters like quantum dots [13], organic molecules [14], etc. The strong field enhancement in the vicinity of a surface allows for attaining the strong-coupling regime [10,11], while a comparatively small mode volume of TPs localized beneath the small metal disk allows using the resonant TP structures to control the spontaneous emission of a semiconductor quantum dot through the Purcell effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer thermal emitters fabricated with a simple deposition process have been demonstrated, and it is also reported that high Q-factor Tamm plasmon (TP) resonance is the key for producing narrowband emission for most designed emitters [19]. Typical designs of Tamm plasmon structures use metal-side structures (incident light from thin metal film) which need an optimized metal thickness [20][21][22]. Since the decay of the electric field inside a metal layer is very fast for the MIR wavelength regime, a metal-side design calls for an ultrathin top metallic layer, and the bandwidth can hardly be controlled.…”
mentioning
confidence: 99%